2012
DOI: 10.5395/rde.2012.37.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic management of a maxillary lateral incisor with dens invaginatus and external root irregularity using cone-beam computed tomography

Abstract: Cone-beam computed tomography (CBCT) is a useful diagnostic tool for identification of both internal and external root configurations. This case report describes the endodontic management of a lateral incisor with both dens invaginatus and external root irregularity by using CBCT. Nonsurgical endodontic retreatment was performed on the lateral incisor with dens invaginatus. A perforation through the dens invaginatus and external concavity was repaired using mineral trioxide aggregate. After 18 mon of follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In the above case, a mesially angulated radiograph uncovered the internal anatomy, but because of inherent disadvantages of intraoral periapical radiographs, application of an advanced imaging modality such as CBCT was found to be valid, given its ability to localize and describe the internal and external anatomy in three dimensions 36,37. However, due to the non-availability of a CBCT unit in the vicinity, an MDCT scan was recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In the above case, a mesially angulated radiograph uncovered the internal anatomy, but because of inherent disadvantages of intraoral periapical radiographs, application of an advanced imaging modality such as CBCT was found to be valid, given its ability to localize and describe the internal and external anatomy in three dimensions 36,37. However, due to the non-availability of a CBCT unit in the vicinity, an MDCT scan was recommended.…”
Section: Discussionmentioning
confidence: 99%
“…However, these radiographs produce only two-dimensional images of three-dimensional objects, resulting in distortion and superimposition of structures. In comparison, more recently developed CBCT scans have significantly improved the understanding of three-dimensional root canal morphology 5,17. CBCT scans can be useful diagnostic tools in endodontic practice since it could help to speculate the location of the canal by referring anatomical structures 18…”
Section: Discussionmentioning
confidence: 99%
“…This generalization is not completely true as reports describe maxillary lateral incisors with two roots or three canals 2,3. Many of these manifest clinically as germination, fusion, concrescence, or dens invaginatus, since maxillary lateral incisors are often located at the site of high embryological risk 4,5. Maxillary lateral incisors can have various configurations of root canals, especially in the Turkish population 6,7.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al also suggested that CBCT is more useful for detection of perforations in the faciolingual plane than conventional radiography (Figure 1). 3…”
Section: Amentioning
confidence: 99%